Diplomacy: Is it still sustainable? - Stefanović-Štambuk Jelica (Međunarodni Problemi, 2010)
Providing the answer to chosen research question on sustainability of diplomacy today is guided by the leading assumption that state is not the sole owner of diplomacy. Relying on ordered existing construction of theoretically and empirically gathered evidence that from its beginnings diplomacy has belonged to every social person and every society the first part of the analysis is used for summing up the indicators and findings why diplomacy could not be enlisted as one of “extinct species”, nor the state for that matter as one of its territorially sovereign entrepreneur. The account of theoretically produced body of knowledge on conditions of sustainable diplomacy is given in the second part. The focus in the third part is on the ongoing turn in understanding of diplomacy. It is growingly realized that its real lair is every social personality and all human societies (historic and geographic). This lair is now theoretically revisited. There are two most visible cognitive results gained. These are the concepts of social entrepreneurship and social power. Concluding remarks are taken for presenting exemplary diplomatic action of one among several of nowadays agile non-territorial sovereigns who by being entrepreneurial in global governance by agreement makes diplomacy sustainable. In wrapping up not only the finding that under existing conditions new forms of diplomatic action of different civil and commercial society entrepreneurs as non-territorial sovereigns make diplomacy sustainable is underlined, but also that it entails the change in entrenched thinking on organizational structure of assenting governance of global affairs.